The Gentlemen's Club: An innovation to improve HIV counselling and testing uptake at a South African university campus - Sogo F. Matlala; Selokela J. Mokono; Pontsho Tsotetsi (AOSIS, 2013)
Background: Many university students were found to be engaging in high HIV risk practiceson campuses which then necessitated discovering their HIV status by participating in HIVcounselling and testing (HCT) campaigns. HCT is an entry point into a comprehensivecontinuum of prevention, treatment, care and support services for HIV infection and AIDS.However, it was also found that many students, mostly males, did not take regular HIV teststo discover their HIV status and receive the necessary counselling and support. Objectives: The innovative Gentlemen's Club was therefore implemented at a universitycampus to increase HCT uptake.The club was formed to motivate male students on behaviourand lifestyle changes so that they could become responsible men. Method: To join the club, a student was required to take a confidential HIV test and as amember he was expected to follow rules of good and responsible behaviour as prescribed bythe club. Results: Club membership and attendance for meetings showed an increase after the launchof the club in 2010 because of its appeal, and there was also a notable increase in the numberof male students attending HCT campaigns. Women have formed a similar club to motivateother women to take regular HIV tests as well. Conclusion: The Gentlemen's Club was an innovative idea that increased HCT uptake by malestudents and served as vehicle to address health and social issues facing university students.